2016
DOI: 10.1016/j.devcel.2016.08.021
|View full text |Cite
|
Sign up to set email alerts
|

A C. elegans Thermosensory Circuit Regulates Longevity through crh-1 /CREB-Dependent flp-6 Neuropeptide Signaling

Abstract: Sensory perception, including thermosensation, shapes longevity in diverse organisms, but longevity-modulating signals from the sensory neurons are largely obscure. Here we show that CRH-1/CREB activation by CMK-1/CaMKI in the AFD thermosensory neuron is a key mechanism that maintains lifespan at warm temperatures in C. elegans. In response to temperature rise and crh-1 activation, the AFD neurons produce and secrete the FMRFamide neuropeptide FLP-6. Both CRH-1 and FLP-6 are necessary and sufficient for longev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 44 publications
8
75
0
Order By: Relevance
“…Importantly, crh-1(-) mutants exhibit a significant delay in age-dependent reproductive decline without prolonged longevity. Consistent with previous results (Chen et al, 2016; Lakhina et al, 2015), crh-1(-) mutants are not long lived (Figure 1E); in fact, crh-1(-) mutants had a slightly reduced lifespan compared to wild type, as has been previously observed (Chen et al, 2016). Therefore, CREB is specifically involved in regulating oocyte quality maintenance without exerting corresponding effects on somatic tissue maintenance.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Importantly, crh-1(-) mutants exhibit a significant delay in age-dependent reproductive decline without prolonged longevity. Consistent with previous results (Chen et al, 2016; Lakhina et al, 2015), crh-1(-) mutants are not long lived (Figure 1E); in fact, crh-1(-) mutants had a slightly reduced lifespan compared to wild type, as has been previously observed (Chen et al, 2016). Therefore, CREB is specifically involved in regulating oocyte quality maintenance without exerting corresponding effects on somatic tissue maintenance.…”
Section: Resultssupporting
confidence: 93%
“…Similar to mammals, CREB is required for longterm associative memory in C. elegans (Kauffman et al, 2010), and also affects C. elegans growth, development and metabolic processes (Lakhina et al, 2015), pointing to a potential role in regulating aging phenotypes. Although our lab and others showed that severe loss-of-function or null mutation of crh-1 , the gene encoding the C. elegans homolog of mammalian CREB, does not extend lifespan (Chen et al, 2016; Lakhina et al, 2015), its role in reproductive aging had not been previously described.…”
Section: Introductionmentioning
confidence: 94%
“…The conserved site of phosphorylation in the transactivation/KID domain of nematode CREB/CRH-1 has been determined to be Ser29, and previous studies showed that an S29A mutant construct was unable to give rise to CaMKIV/CMK-1 or CaMKK/CKK-1-induced transcription by CRH-1. The use of the S133/S29 phosphorylation site in nematode CRH-1 has been confirmed by several additional studies (Kauffman et al 2010;Chen et al 2016;Freytag et al 2017). In contrast, the sequence of other CREB regulatory phosphorylation sites used in mammals (Mayr and Montminy 2001;Deisseroth and Tsien 2002;Lonze and Ginty 2002;West et al 2002;Altarejos and Montminy 2011) is not conserved in nematode CRH-1 (not shown; we do not exclude the possibility that non-typical phosphorylation sites in CRH-1 might be recognized in the future, but these have not been demonstrated so far).…”
Section: Creb/crh-1 Activity In Nematode Excitotoxicity Is Cell Autonmentioning
confidence: 63%
“…GluRs mediate both basic signaling and synaptic plasticity (Rose et al 2003(Rose et al , 2005Rose and Rankin 2006;Emtage et al 2009;Stetak et al 2009). CREB (worm homolog name: CRH-1) and the components of its canonical activation cascade are also well conserved in the worm, and regulate learning and memory and synaptic plasticity Bates et al 2006;Suo et al 2006;Kauffman et al 2010;Nishida et al 2011;Timbers and Rankin 2011;Yu et al 2014;Lakhina et al 2015;Chen et al 2016;Moss et al 2016;Freytag et al 2017;Nishijima and Maruyama 2017;Arey et al 2018;Kaletsky et al 2018). CREB/CRH-1 can be activated by phosphorylation (on a site homologous to Ser133) by the nematode's combined CaMK I/IV homolog CMK-1, whose basal activity is greatly stimulated by CaMKK/CKK-1 Yu et al 2014) (while the other CREB phosphorylation sites seen in mammals do not seem to be conserved in the nematode).…”
mentioning
confidence: 99%
“…AFD neurons transmit signals that sustain a normal life span at warmer temperatures (25°C). Elevated temperature elicits CMK-1-dependent flp-6 gene expression in AFD (64). FLP-6, an FMRFamide family peptide, is released as an NT at the AFD-AIY interneuron synapse, thereby regulating thermosensory circuitry.…”
Section: Discussionmentioning
confidence: 99%